Experimental Study on the Wear Mechanisms of Cutting Tools in High-Performance Machining - Amit Shishodia (International Journal of Fracture Mechanics and Damage Science, 2024)
Because high-performance machining (HPM) may increase output and improve product quality, it is essential for modern production. The quick wear of cutting tools under high-stress circumstances, however, presents serious difficulties that affect surface smoothness, tool life, and cost-effectiveness. Through an analysis of the impacts of cutting speed, feed rate, tool material, and cooling techniques, this work explores the wear processes impacting cutting tools in HPM. Advanced spectroscopy and microscopy procedures were used to characterize wear patterns and processes. The results show that fatigue wear caused by abrasive, adhesive, diffusion, oxidation, and thermal-mechanical processes is common and that different machining settings affect these systems. Notably, it turned out that minimum quantity lubrication (MQL) efficiently mitigates adhesive wear. This research contributes to the creation of more effective and long-lasting HPM processes by offering vital insights for maximizing tool performance and prolonging tool life.
Keywords: EDS; High-performance machining; SEM; XRD; minimum quantity lubrication